Pengaruh Financial Literacy dan Financial Behavior terhadap Keputusan Investasi pada Ibu-Ibu PKK Kota Jambi - Indah Mutiara; Efandri Agustian (Universitas Batanghari, 2020)
This study aims to determine the level of influence of Financial Literacy and Financial Behavior toward investment decisions. The data used in this study are primary data, the sample used in this study were PKK members in Jambi City. The sampling technique was carried out by using purposive sampling method. The results obtained by using multiple linear regression test Y = 2,337 + 0.159 X1 + 0.518 X2, and the test of this study using the f-test, R2-test and t-test. The results of this study indicate that partially the Financial Literacy and Financial Behavior affect investment decisions.